Study of Land Productivity in Composting Process of Tea Solid Waste at PT. Gunung Slamat - Tafrijiyah, Antika; Widiyanto, Bayu; Elfiana, Nia (Agroindustrial Journal, 2023)
PT. Gunung Slamat, as a company operating in the tea processing industry, was founded by the Sosrodjojo family. This scientific article aims to analyze land productivity in composting solid tea waste at PT. Gunung Slamat by considering land area, waste processing capacity, and providing recommendations for solutions that can significantly increase the productivity of solid tea waste processing land. The research adopts a phenomenological approach to obtain the required data. Phenomenology is defined as a type of research that seeks to analyze descriptively and introspectively various forms of human consciousness and experience. Data obtained from quantitative observations will cover various aspects such as the amount of compost produced, the time required to process waste into compost, which will then be collected and analyzed. The compost produced from waste processing at PT. Gunung Slamat is used as fertilizer within the company's environment and distributed to local farmers, benefiting both the environment and the local community. This compost product is not sold because PT. Gunung Slamat focuses more on selling tea products. In waste processing, several issues have been identified, including a lack of suitable technology for utilizing tea waste. The research findings indicate that land productivity in composting solid tea waste fluctuates during the study period, with changes associated with various factors such as waste quantity, weather, and management practices. Further evaluation of the factors influencing land productivity, along with the implementation of more advanced technology, can enhance efficiency and have a positive impact on the environment.